Spectroscopic quantification of soil phosphorus forms by 31P-NMR after nine years of organic or mineral fertilization Quantificação espectroscópica de formas de fósforo do solo por 31p-rnm após nove anos de uso de fertilizantes orgânicos ou minerais - Gatiboni L.C.* (2013)
Long-standing applications of mineral fertilizers or types of organic wastes such as manure can cause phosphorus (P) accumulation and changes in the accumulated P forms in the soil. The objective of this research was to evaluate the forms of P accumulated in soils treated with mineral fertilizer or different types of manure in a long-term experiment. Soil was sampled from the 0-5 cm layer of plots fertilized with five different nutrient sources for nine years: 1) control without fertilizer; 2) mineral fertilizer at recommended rates for local conditions; 3) 5 t ha-1 year-1 of moist poultry litter; 4) 60 m3 ha-1 year-1 of liquid cattle manure and 5) 40 m3 ha-1 year-1 of liquid swine manure. The 31P-NMR spectra of soil extracts detected the following P compounds: orthophosphate, pyrophosphate, inositol phosphate, glycerophosphate, and DNA. The use of organic or mineral fertilizer over nine years did not change the soil P forms but influenced their concentration. Fertilization with mineral or organic fertilizers stimulated P accumulation in inorganic forms. Highest inositol phosphate levels were observed after fertilization with any kind of manure and highest organic P concentration in glycerophosphate form in after mineral or no fertilization.